The Self‐enhancement Function of Autobiographical Memory. Issue 1 (18th September 2014) - Demiray, Burcu; Janssen, Steve M. J.
Summary The self‐enhancement function of autobiographical memory was examined by assessing the psychological distance of adults' most important memories. Participants (N = 445, ages 18–80) reported the seven most important events from their lives on an online survey and rated the memories in terms of valence, emotionality, importance, vividness, reliving, rehearsal, novelty, and psychological distance. Participants also completed the Rosenberg Self‐esteem Scale. Regression analyses showed that participants felt psychologically closer to positive memories than to negative memories, independent of the actual age of the memories. The self‐enhancement function was unrelated to participants' age but was related to their self‐esteem: Higher self‐esteem was associated with feeling closer to positive memories. Finally, a moderated multiple‐mediation model showed that memories' importance and rehearsal mediated the relation between one's self‐esteem and the psychological distance of their positive versus negative memories. Findings are discussed in relation to the functional approach to autobiographical memory. Copyright © 2014 John Wiley & Sons, Ltd.